2019
DOI: 10.1038/s41467-019-11777-7
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA CircFndc3b modulates cardiac repair after myocardial infarction via FUS/VEGF-A axis

Abstract: Circular RNAs are generated from many protein-coding genes, but their role in cardiovascular health and disease states remains unknown. Here we report identification of circRNA transcripts that are differentially expressed in post myocardial infarction (MI) mouse hearts including circFndc3b which is significantly down-regulated in the post-MI hearts. Notably, the human circFndc3b ortholog is also significantly down-regulated in cardiac tissues of ischemic cardiomyopathy patients. Overexpression of circFndc3b i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
234
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(248 citation statements)
references
References 62 publications
3
234
0
Order By: Relevance
“…Previous studies have revealed that circRNAs play important roles in the regulation of multiple diseases, especially cancers (39)(40)(41)(42). Aberrant expression of circRNAs was also correlated with progression, drug resistance and prognosis of cancers (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that circRNAs play important roles in the regulation of multiple diseases, especially cancers (39)(40)(41)(42). Aberrant expression of circRNAs was also correlated with progression, drug resistance and prognosis of cancers (21).…”
Section: Discussionmentioning
confidence: 99%
“…CircFndc3b could function through interacting with RBP-FUS which regulates the expression and the signaling pathway of vascular endothelial growth factor-A (VEGF-A). The overexpression of circFndc3b in post-MI mouse hearts could decrease cardiomyocyte apoptosis and fibrosis, enhance neovascularization, reduce infarct size and attenuate left ventricular dysfunction after MI ( Garikipati et al, 2019 ). CircTtc3 was reported to be significantly upregulated in rats with MI ( Cai et al, 2019 ).…”
Section: Circrnas and Cardiovascular Diseasesmentioning
confidence: 99%
“…Circular RNA (circRNA) are a class of singlestranded RNA that are covalently closed by linking the 3 0 and 5 0 ends, and many of them have been recognized to be involved in various human diseases as gene regulators [8]. CircFNDC3B is a circRNA that is formed by back-splicing exons 5 and 6 in the FNDC3B gene and has recently been implicated in gastric cancer [9], cardiovascular disease [10], bladder cancer [11] and renal carcinoma [12] by modulation of specific signaling pathways. However, the expression level of circFNDC3B and its underlying molecular mechanisms in CRC have never been reported.…”
Section: Introductionmentioning
confidence: 99%